Corporate Fundamentals, Bi Rate And Systematic Risk: Evidence From Indonesia Stock Exchange - Nita Puspitasari, Perdana Wahyu Santosa, (Jurnal Manajemen, 2019)
The aim of this study is to understand the effect of company's fundamental factors and BI rate on systematic risk (beta) on the Indonesia Stock Exchange (IDX). In portfolio theory, there are two types of risk, namely systematic risk and non-systematic risk. The focus of this study is on systematic risk which was measured through beta (β), where each stock had a different beta. The analyses used independent variables of sales growth (SG), net profit margin (NPM), debt to equity ratio (DER) and BI rate (benchmark interest rate) on stock beta. The data used were quarterly data of issuers listedin the LQ-45 index in the period of 2009-2016 which were analysed using panel data regression method. The conclusion from panel data analysis of LQ-45 index is that SG, NPM and DER contribute a significant impact on systematic risk, but the macroeconomic proxy, namelyBI rate, does not offer significant influence on stock beta (β).Implication: corporate fundamental factors such as sales growth, net profit margin and solvency has effect significantly on beta (β), however BI rate does not.